Addition of cladribine to the standard induction treatment improves outcomes in a subset of elderly acute myeloid leukemia patients. Results of a randomized Polish Adult Leukemia Group (PALG) phase II trial. Issue 4 (13th February 2017) - Pluta, Agnieszka; Robak, Tadeusz; Wrzesien‐Kus, Agata; Katarzyna Budziszewska, Bozena; Sulek, Kazimierz; Wawrzyniak, Ewa; Czemerska, Magdalena; Zwolinska, Malgorzata; Golos, Aleksandra; Holowiecka‐Goral, Aleksandra; Kyrcz‐Krzemien, Slawomira; Piszcz, Jaroslaw; et al.
Abstract: Intensive induction chemotherapy using anthracycline and cytarabine backbone is considered the most effective upfront therapy in physically fit older patients with acute myeloid leukemia (AML). However, outcomes of the standard induction in elderly AML are inferior to those observed in younger patients, and they are still unsatisfactory. As addition of cladribine to the standard induction therapy is known to improve outcome in younger AML patients. The present randomized phase II study compares efficacy and toxicity of the DAC (daunorubicin plus cytarabine plus cladribine) regimen with the standard DA (daunorubicin plus cytarabine) regimen in the newly diagnosed AML patients over 60 years of age. A total of 171 patients were enrolled in the study (DA, 86; DAC, 85). A trend toward higher complete remission (CR) was observed in the DAC arm compared to the DA arm (44% vs. 34%; P  = .19), which did not lead to improved median overall survival, which in the case of the DAC group was 8.6 months compared to in 9.1 months in the DA group ( P  = .64). However, DAC appeared to be superior in the group of patients aged 60‐65 (CR rate: DAC 51% vs. DA 29%; P  = .02). What is more, a subgroup of patients, with good and intermediate karyotypes, benefited from addition of cladribine also in terms of overall survival ( P  = .02). No differences in hematological and nonhematological toxicity between the DA and DAC regimens were observed.